Organizing age - Fineman, Stephen (Oxford University Press, 2011)
Age is the silent shaper of work organizations and their human resource practices. It has become a potent feature of how society is structured and how it views itself. Age assumptions mould the behaviours of young and old alike, and are used as political tools by policy makers and managers. Organizing Age asks the perennial question - can age ever not matter? Drawing on range of social scientific and popular writings, this book casts a critical eye over the social construction and politicization of age in and beyond organizations. Amongst other topics, it discusses: the historical roots of age.